가죽 소재를 활용한 텍스타일디자인 연구 - 베지터블가죽의 철염을 중심으로 - 강기용; Kang Ki Yong (기초조형학연구, 2020)
본 연구는 가죽 소재에 활용 가능한 염색기법을 연구하여 텍스타일디자인으로 개발하고, 나아가 패션 소품으로의 제작 가능성을 모색함으로써 섬유패션산업에 지속 가능한 텍스타일디자인 소재개발의 방향을 제시하고자 하였다. 기존 가죽염색 연구는 색상표현이나 가죽의 질감표현을 중심으로 하고 있으나, 가죽의 문양 염색에 의한 텍스타일디자인 연구는 부족하다. 또한, 개인이 가죽 가공기술을 접하거나 가죽에 문양을 염색하여 텍스타일디자인에 적용한다는 것은 많은 어려움을 동반한다. 이러한 점을 고려하여 가죽의 염색방법을 중심으로 텍스타일디자인 표현기법을 연구 개발하고자 하였다. 이에 누구나 쉽게 염색을 할 수 있도록 염료 수급의 편의성, 염액추출의 용이성, 염색방법의 수월성을 실험의 조건으로 베지터블가죽에 천연염색의 커피염색, 화학염색의 가죽용 알코올염료염색, 매염염색의 탄닌과 철의 반응에 의한 철염, 세 종류 염색기법을 실험하고 문제점을 도출하였다. 또한, 철의 반응에 의한 염색기법을 철염(Iron dyeing)이라고 칭하고, 우리 주변에서 쉽게 접할 수 있는 여러 가지 철재용구의 형태를 사용하여 다양한 문양의 텍스타일디자인을 연구 제작하였다. 그 결과 가죽에 활용한 철염은 누구나 쉽고 간단하게 친숙한 문양의 텍스타일디자인 표현이 가능하였으며, 염료를 사용하지 않는 친환경적 지속 가능한 가치를 높일 수 있어, 지금까지의 가죽염색 가공기법과는 차별화된 염색기법임을 확인할 수 있었다. 이러한 철염에 의해 제작된 디자인의 활용 가능성을 모색하고자 수공예 기법으로 패션 소품으로 연계하여 가방 등 17점을 제작하였다. 본 연구를 통해 가죽염색 가공이 어렵다는 선입견의 해소와 철염에 의한 텍스타일디자인의 표현기법을 확대하고, 나아가 가죽을 활용한 텍스타일디자인의 소재개발에 도움이 되고자 한다. This study aims to develop textile design by researching dyeing techniques that can be applied to leather materials and to suggest the direction of sustainable textile design material development in the textile fashion industry by searching for the possibility of fashion accessory production. The existing researches on leather dyeing are centered on color expression or texture expression of leather, and there is a lack of research on a textile design by dyeing leather patterns. In addition, it is difficult for an individual to encounter leather processing technology or to dye a pattern on the leather and apply it to textile design. Considering these aspects, we tried to research and develop the textile design expression technique based on the dyeing method of leather. In order to make it easy for anyone to dye, the convenience of dye supply, the ease of salt extraction, the easiness of the dyeing method are set as experimental conditions. Then, three dyeing techniques, coffee dyeing, alcohol dye dyeing, and iron salting, were tested on vegetable leathers. In addition, this study defined the dyeing method according to the iron reaction as iron salt and studied textile designs of various patterns using various types of steel tools that can be easily encountered around us. As a result, iron salt used in leather could express the textile design of familiar patterns easily and simply, and it could emphasize environmentally sustainable value without using dye. It was confirmed that this is a dyeing technique different from the existing leather dyeing processing technique. In order to explore the applicability of the designs produced by iron salts, 17 items including bags were produced in connection with fashion items using handicraft techniques. This study resolves the prejudice that leather dyeing is difficult and expands the expression techniques of various textile designs by iron dyeing. In addition, it will help to expand the material development of textile design using leather.